How to make money while being a student in Ukraine - Pliasetska, V. (ТДАТУ, 2018)
The main purpose of the article is to solve the problem by identifying and familiarizing with perspective activities, where students can earn money, and possible places of work that will not interfere with studying and take away all the free time.
Keywords: free time; students; earn money; labor market